Identitas Budaya Masyarakat Kota: Teater Tradisi di Kota Surabaya Pada Awal Abad XX - S. Samidi (Indonesian Historical Studies, 2019)
This study examines why does Ludruk represent the cultural identity of the people of Surabaya? How does society appreciate the traditional theater, especially in Ludruk in their daily practice? The purpose of this article explains the historical reality of Ludruk art that serves as entertainment and cultural identity. This article using the historical method by relying on historical sources. The result shows that theater traditions that existed and famous in Surabaya at the beginning of the 20th century were Comedy Stambul, Wayang Wong, and Ludruk, then appeared Ketoprak in the late 1930s. The appearance of this theater has been adapted to the tastes of the support community. Comedy Stambul is a theater that originated in India, then spread to Southeast Asia. Comedy Stambul is considered as a hybrid art because it comes from a blend of local cultural elements, while Wayang Wong, Ludruk, and Ketoprak an original art derived from customs and local values. Theater that represents the cultural identity of the people of Surabaya is Ludruk.